Staged Show Trials, Political Theater, and the Aesthetics of Judgment - Arjomand, Minou 1984- (Columbia University Press, 2018)
Minou Arjomand draws on a rich archive of postwar German and American performances to reveal theater as a place for forms of judgment that are inadmissible in a courtroom but indispensable for public life. Staged weaves together theater history and political philosophy into a powerful case for the importance of theaters as democratic institutions.